The Effectiveness of Realistic Mathematics Education on Learning Outcomes and Critical Thinking for Elementary School Students - Widiana, Aida Nur; Sintawati, Mukti; Abdurrahman, Ginanjar (International Journal of Learning Reformation in Elementary Education, 2023)
Implementing learning on mathematics material that does not provide facilities for students to explore critical thinking skills results in a lack of student learning outcomes. The teacher-centred learning process makes many students passive when learning takes place, and low student learning outcomes and critical thinking are also caused by the use of less varied learning models. This makes researchers apply an approach with PMRI (Pendidikan Matematika Realistik Indonesia or Indonesian Realistic Mathematics Education). This study aimed to determine the effectiveness of PMRI in improving fourth-grade students' learning outcomes and critical thinking. This research was a pre-experimental study; the subjects in this study were fourth-grade students with 20 students. The design in this study is quasi-experimental with the form of one group pretest-posttest design. Data collection was carried out using test, observation and documentation techniques. Data analysis techniques were carried out by Normality Test, Homogeneity Test, and Paired t-test. The results showed that PMRI learning can improve students' learning outcomes and critical thinking. This is evidenced by the average value of learning outcomes pretest (69.65) and post-test (87.35). Then the average value of critical thinking at the first meeting (68.05) and the second meeting (78.85). The conclusion that can be drawn is that students' learning outcomes and critical thinking have increased after PMRI was applied to fourth-grade students.